Preparation and properties of silver-containing composites based on melamine-formaldehyde polymer modified with diisocyanate oligomers of different structures - Tolstov, A. L.; Kobrina, L. V.; Klymchuk, D. A.; Matyushov, V. F.; Lebedev, E. V. (Reports of the National Academy of Sciences of Ukraine, 2016)
Silver-containing composites were prepared via the sorption of silver ions by melamine-formaldehyde polymer (MFP) modified with diisocyanate oligomers. Introducing the modifiers into a structure of MFP improves microphase separation processes and increases the permeability of the matrix and the concentration of coordination active functional groups. Sorption capacity of modified MFP to Ag+ ions reaches 6.5 · 10−2 g/g. Ag-containing nanocomposites obtained are characterized by a heterogeneous structure, increased hydrophilicity, and gradient distribution of silver in a bulk of the polymers.